Case report: Surgical resection of a retro-hepatic leiomyosarcoma involving atrial reconstruction, cardiopulmonary bypass, ex vivo tumor resection, and liver re-implantation - Sharma, Neel K.; Okakpu, Uchenna; Murthy, Jeevan; Wei, Lawrence M.; Lopez-Solis, Roberto; Schmidt, Carl; Badhwar, Vinay; Marsh, J. Wallis (Frontiers in Surgery, 2022)
Introduction Leiomyosarcomas (LMS) involving the inferior vena cava (IVC) is a clinically rare entity, accounting for approximately 0.5% of all adult sarcomas. Case presentation A 67-year-old male presented to the emergency department with mild back and lower abdominal pain. During the workup, a computed tomography scan without contrast showed an area of decreased attenuation within the liver adjacent to the intrahepatic IVC. Magnetic resonance imaging confirmed the involvement of the retro-hepatic IVC; biopsy confirmed the diagnosis of LMS. Given the location of the involvement of the retro-hepatic IVC, liver explantation was deemed necessary for adequate tumor resection. The superior extension of the tumor toward the heart necessitated Cardio-Pulmonary (CPB). The patient successfully underwent a complex surgical procedure involving liver explantation with ex vivo back-table resection of the retro-hepatic LMS, replacement of the retro-hepatic vena cava with a ringed Gore-Tex graft, liver re-implantation, and hepatic vein-atrial reconstruction under cardiopulmonary bypass. There were no intraoperative or post-op complications. Discussion The role of vascular reconstruction of the IVC varies depending on the level and extent of the tumor, with options ranging from primary repair, ligation, or reconstruction dictated. Surgical resection with negative margins remains the treatment of choice due to the lack of efficacy of adjuvant therapies. Importantly, liver explantation offers a chance for complete surgical resection and reconstruction. Similarly, the complex nature of the tumor necessitated a pioneering approach involving direct hepato-atrial venous anastomosis. Conclusion To the best of our knowledge, this is the first reported case in which the hepatic veins were anastomosed directly to the right atrium while also replacing the native vena cava with a separate graft.